Non-Abelian Constructivist Lagrangian (JOURNAL OF ADVANCES IN PHYSICS, 2023)
A whole Yang-Mills symmetry is proposed. A grouping physics is constituted. It consists in inserting a given Yang-Mills field Aaμ in a fields set Aa μI constituted by other fields families, I = 1, . . . , N. Each field becomes part of a whole. A set action physics happens preserving the Yang-Mills symmetry. However the usual properties of an isolated field are extended to antireductionist properties. An associative physics is formed. A Yang-Mills whole quantum system is constituted. A whole Yang-Mills physics isobtained. The quantum corresponding to a specific Aa μI field inserted in a whole develops features depending on thefields set Aa μI associativity. Properties established from a so-called constructivist gauge theory are identified. Usual YM interactions are enlarged to YM interrelationships. Classical equations are studied under set action. A Yang-Mills whole unity is constituted by a constructivist Lagrangian. The reductionist approach substituted by constructivism. Physics under set transformations. A cause and effect relationship is expressed based on whole unity. The whole is that moves to future. Minimal action principle, Noether theorem, Bianchi identities are derived. A fields set with diversity, interdependence, nonlinearity, chance is expressed.